Ethnobotanical Study on Medicinal Plants in Villages of Adaklı (Bingöl-Turkey) - Doğan, Gülden; Durumlu, Muhammed (Uğur ÇAKILCIOĞLU, 2024)
In an ethnobotanical study carried out in the Adaklı (Bingöl) region between 2021 and 2023, 150 plant taxa belonging to 42 families and 125 genera were detected. In the research area, local people use wild plants mostly for medicinal (104) and food (89) purposes, and in small amounts for fuel, fodder, brooms, etc. In this article, wild plant taxa (104) determined to be used by the local people for medicinal purposes are included. Local names, parts used and areas of use of these medicinal plants were determined. The plants used in Adaklı are known by the same or different local names in various parts of Anatolia. Plants with medicinal uses mostly belong to the Astreaceae (14 taxa), Rosaceae (10 taxa), Lamiaceae (10 taxa), Fabaceae (7 taxa) and Apiaceae (5 taxa) families. It has been determined that medicinal plants are used in the treatment of many diseases, especially colds, shortness of breath, heart and gastrointestinal diseases.
Keywords: Botany (Other); Bitki Bilimi (Diğer)